Pengaruh Pengukuran Kinerja Keuangan Perusahaan terhadap Return Saham Perusahaan Manufaktur yang Terdaftar di BEJ - Swastika, Dwi Lusi Tyasing (Akutansi Bisnis & Manajemen ( ABM ), 2007)
The objective of this research is to analyze the influence of company’s performance in EPS and MVA on stock return. The research sample totaled 297 manufacturing companies which listed and traded in Jakarta Stock exchange. The period od this study is 2002 – 2004. The data puts from JSX Monthly Review and Indonesian Capital Market Directory. The statistic method used is multiple regression. The result of this research are: (1) the influence of company’s performance in EPS and MVA on stock return gave positive influence and significant; (2) the influence of EPS on stock return gave dominant influence.